(untitled) (Journal of Informatics Education and Research, 2026)
This study employs a 21-item Likert scale questionnaire (5 points) to examine how entrepreneurial-oriented factors i.e., Competitive Aggressiveness, Autonomy affect proactiveness and business performance. The sample comprised 376 MSMEs owners from the Uttar Pradesh Services MSMEs. For this study, proprietors of MSMEs were specifically selected. The objective of the present study is to study the impact of Competitive Aggressiveness and autonomy on Business Performance, and Proactiveness in selected MSMEs in Uttar Pradesh. The data are collected both online and offline. Smart PLS 4 software is used for analyzing the data and hypothesis testing. The study found that both Competitive Aggressiveness and Autonomy positively impact Business Performance and Proactiveness. Therefore, all the hypotheses formulated are accepted. In this study, two new relationships are shown. These results provide fresh insight into the variables influencing aspiring entrepreneurs, making them significant. Thereby adding a substantial theoretical contribution to the knowledge of entrepreneurial orientation. This study offers significant practical value to policymakers seeking to identify and develop potential entrepreneurs into successful ones, as nations recognize innovation and entrepreneurship’s role in boosting their global competitiveness.